2020
DOI: 10.1177/2045894020966889
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for 30‐day readmission in adults hospitalized for pulmonary hypertension

Abstract: Readmissions for pulmonary hypertension are poorly understood and understudied. We sought to determine national estimates and risk factors for 30-day readmission after pulmonary hypertension-related hospitalizations. We utilized the Healthcare Cost and Utilization Project Nationwide Readmission Database, which has weighted estimates of roughly 35 million discharges in the US. Adult patients with primary International Classification of Disease, Ninth Revision, Clinical Modification diagnosis codes of 416.0 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Costs data for this study were obtained from HCUPnet, which is sponsored by AHRQ 20 . While costs may not be exact for patients with PD, there are studies that have utilized AHRQ as a source to derive costs data in other disease states [29][30][31] . In our study, the higher level of HCRU reported for patients experiencing "OFF" episodes was reflected in higher healthcare costs than those in patients not experiencing "OFF" episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Costs data for this study were obtained from HCUPnet, which is sponsored by AHRQ 20 . While costs may not be exact for patients with PD, there are studies that have utilized AHRQ as a source to derive costs data in other disease states [29][30][31] . In our study, the higher level of HCRU reported for patients experiencing "OFF" episodes was reflected in higher healthcare costs than those in patients not experiencing "OFF" episodes.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 32 variables associated with readmission were collected according to relevant studies and clinical availability ( 7 , 15 ), including patient demographics (gender and age), length of stay (LOS), etiology of PH, comorbidities, targeted pharmacotherapy for PH during hospitalization, use of mechanical ventilation, and nonmedical order discharge. All data for included variables were extracted from inpatient electronic medical records.…”
Section: Methodsmentioning
confidence: 99%